Rational use of water in car dealership - Marques, Alcides Junio Lemes; Silva, Sarah Barbacena; Cruvinel, Karla Alcione da Silva; Ferreira, Evaldo de Melo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The various uses of water by man are related to their availability and socio-economic reality, considering that to achieve economic development many countries have consumed the action on a large scale. It is estimated that the current consumption of water has increased six-fold over the past century, causing lack of water in front of excessive consumption. Losses in buildings may cause the increased demand of appeal. When it comes to building, an example may be cited of a potential consumer of water are the car dealerships, the object of study. In this project the use of water is distributed in the washing vehicles and parts, consumables for cleaning large area, garden irrigation, and their own consumption. It an average monthly expenditure of 330 m³ per month occurs. The car wash is the main consumer of water in the venture, coming to consume 293.88 m³ per month. Implement a program for the rational use in undertaking of this size in order to minimize waste and reduce the amount paid monthly tariff and the most importance.